Break Point Distance Path Loss Model for Indoor Wireless Communications with Equivalent Floor - Supachai Phaiboon (2021)
© 2020 IEEE. This paper presents break point distance path loss models with equivalence floor for 5G millimeter wave (mmWave). The proposed model consists of dual slope path losses which are in distances before and after breakpoint together with additional wall attenuation loss. In case of non-line-of-sight (NLOS), shadowing caused by obstacles will appear with equivalent floor and raise ground reflection caused by furniture and exiting multi-wall attenuation loss. Comparison between two types of buildings show that the equivalence floor and total wall attenuation provide a characteristic of the buildings which influence on wave propagation as well.